ChemInform Abstract: Advances in Click Chemistry for Silica‐Based Material Construction. Issue 16 (March 2016) - Mohammadi Ziarani, Ghodsi; Hassanzadeh, Zahra; Gholamzadeh, Parisa; Asadi, Shima; Badiei, Alireza
Abstract: Review: 105 refs.